2020
DOI: 10.14254/2071-8330.2020/13-2/23
|View full text |Cite
|
Sign up to set email alerts
|

Social safety and behavioral aspects of populations financial inclusion: A multicountry analysis

Abstract: This article aims to investigate the connection between behavioral aspects of populations financial inclusion and the level of social safety. The study was conducted in several stages: collecting the necessary input, determining The Index of socio-safety, selecting the most relevant factors that characterize the behavioral aspects of financial inclusion, determining the functional relationships between The Index of socio-safety and indicators describing critical behavioral issues of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Authors (Çera et al, 2019;Kashyap et al, 2020) used the principal component analysis and non-parametric methods to explore the linkages between entrepreneurial and social factors. The paper (Didenko et al, 2020a) investigated the relationship between behavioral aspects of populations' financial inclusion and social safety level. Authors (Mihi-Ramire et al, 2020;Bagmet et al, 2018) concluded that social strategies and policies use and promote the interaction between employer mobility factors since they allow companies and employees to diversify their risks and find new trade and investment opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors (Çera et al, 2019;Kashyap et al, 2020) used the principal component analysis and non-parametric methods to explore the linkages between entrepreneurial and social factors. The paper (Didenko et al, 2020a) investigated the relationship between behavioral aspects of populations' financial inclusion and social safety level. Authors (Mihi-Ramire et al, 2020;Bagmet et al, 2018) concluded that social strategies and policies use and promote the interaction between employer mobility factors since they allow companies and employees to diversify their risks and find new trade and investment opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research of economic and social processes as an element of the country's brand are discussed in the following studies [13][14][15][16][17]. The COVID-19 pandemic has made great adjustments in all areas of business and people's lives, including branding and consumers' behaviour [18][19][20][21]. The impact of Covid-19 pandemic is discussed in [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3]; 2) forecasts are made mainly in the medium term and are adjusted on average once a year [4,5,6,7]; 3) many models consider the impact of technological and social changes in the economy, global economic conditions, changes in consumer preferences, productivity, labor and geographical mobility of the population on future demand for labor and their supply [8,9,10,11]; 4) most models use quantitative economic and mathematical methods (econometric methods, intersectoral balance matrices, macroeconomic modeling, analysis of structural changes, etc.) [12,13,14,15]. Most of these models particularly use large and complex data sets.…”
Section: Introductionmentioning
confidence: 99%